Rethinking plant protein extraction: Albumin—From side stream to an excellent foaming ingredient. (January 2022) - Yang, Jack; Kornet, Remco; Diedericks, Claudine F.; Yang, Qiuhuizi; Berton-Carabin, Claire C.; Nikiforidis, Constantinos V.; Venema, Paul; van der Linden, Erik; Sagis, Leonard M.C.
Abstract: The transition from animal- to plant-derived dietary proteins is of global importance. Plant proteins are normally processed into extracts, and due to the type of process, proteins from the globulin class are mainly extracted. Such extractions have several waste streams, containing another protein class: albumins. Here, we show that plant albumins have good functionality. We compared interfacial and foaming properties of albumins and globulins from mung bean, Bambara groundnut and yellow pea. The foaming properties of albumins were good, similar or even superior to those of whey or egg white proteins, while globulin-based foams showed low stability. Albumins form strong cohesive interfacial layers around air bubbles. Globulins are unable to create such layers, mainly due to their aggregated structures. Additionally, we provide a mild extraction method, allowing the co-extraction of albumin and globulin. This protein mixture is able to form foam with half-life times up to 450 min. Though currently underutilized, plant albumins can substitute animal proteins, especially in foaming applications, where they outcompete globulins. Their utilization could be an important contribution to the food protein transition. Graphical Abstract: ga1 Highlights: Globulin extraction generates a waste stream, containing albumins. Albumins and globulins from three plant sources were compared. Globulins formed weak interfacial films, leading to poor foam stability. Albumin-stabilized foams were similarly stable as whey protein-stabilized ones. Co-extraction of albumins and globulins also result in a good foaming ingredient.